Citizenship and multiculturalism: towards an agenda for education for Macau - Chan, Chi Hou (University of Saint Joseph, 2002)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Learning English in Macao - Cheong, Kit U. (University of Saint Joseph, 2002)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A case study of the English class council of form 5B (Yuet Wah College, Macau school year 1999-2000): towards a participatory and transformative approach in education - Ching, Desiderio (University of Saint Joseph, 2002)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

College choice: how students in Macau choose thier higher education institution - Coimbra, Diamantina Luiza do Rosario Sa (University of Saint Joseph, 2002)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Suicide prevention in schools: are Macau's teachers prepared? - Diaz, Javier Suarez (University of Saint Joseph, 2002)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Understading parental involvement from a socio-cultural perspective - Ao, Sio Heng (Macau Inter-University Institute, 2003)
Keywords: Parent-teacher relationship; Thesis and Dissertations Master of Education (MED); University of Saint Joseph

An analysis of leadership in school - Ao, Wai Ngán (University of Saint Joseph, 2003)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Teachers stress in the workplace in Macau: an investigation - Chan, Chao Hou (University of Saint Joseph, 2003)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

The use of multimedia in primary teaching: a case study - Lam, Szui Lui (University of Saint Joseph, 2003)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Class size, student achievement and pedagogical principles - Noruega, Charlot Francisca Fernandes (University of Saint Joseph, 2003)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Student councils and citizenship eduation: Principles and practices - Tang, Sut Leong (University of Saint Joseph, 2003)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Action research, information technology and chemistry teaching in a Macau secondary school - Tchiang Van Man, Isabel (University of Saint Joseph, 2003)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

An investigation into the competence-based approach and the person-centered approach for an all-round teaching approach, with reference to the aims of education - Un, Molly (University of Saint Joseph, 2003)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Misbehavior in school: problems and solutions - Cheong, Chun Cheng (University of Saint Joseph, 2004)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Motivation as a key factor in the learning of English as a second language in Macau - Chiang, In Wa (University of Saint Joseph, 2004)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

An investigation into issues for leadership in culturally diverse schools - Hough, Elayne (University of Saint Joseph, 2004)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Perspectives on extra-curricular activities in a secondary school: a survey - Lai, Ka Lon (University of Saint Joseph, 2004)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

An analysis of whether collaborative and cooperative work can improve students' reading and writing in English and enhance the development of higher order thinking - Lai, Pak Cheong (University of Saint Joseph, 2004)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

The implementation of the theory of multiple intelligences in the primary section of a school in Macau - Vong Ka I, Catherine (Macau Inter-University Institute, 2004)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

First year parenting and infant development: some implications for parenting education - Yan, Son U. (University of Saint Joseph, 2004)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Does gender make a difference in English language learning and attainment of secondary school students in Macau: a case study - Leong, On No (University of Saint Joseph, 2005)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Teacher stress in the Macau workplace - Garcia, Alejandro Salcedo (Inter-University Institute of Macau, 2008)

A process-genre approch in curriculum development for lawyers in Macao: a case study - Fernandes, Raquel de Senna (University of Saint Joseph, 2009)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Knowledge management in a Macao public sector bureau: a case study - Tai, Kin Ip (University of Saint Joseph, 2009)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Parents, students and secondary schools in Macao - Tchiang, Van Man (University of Saint Joseph, 2009)
Macao, a developing city, has been undergoing rapid and significant changes economically, culturally, and socially, partly as a consequence of the changes to the economy brought about by the gaming and tourism industry. Changes in Macao have had a major impact on its schools. Parents have a significant impact on students in school, and Macao’s secondary schools are having to handle a range of challenges and problems brought by students and their parents, many of these as a result of the changes in the wider society of Macao. The response of many schools to the challenges faced is limited, and they understate and under-use the important role played by more developed forms of parental involvement in schools. This study examines the nature, scope and extent of the problems that secondary schools in Macao are having to handle from parents and students, how the schools are handling them, and what needs to be done in order to address the problems and handle them more effectively. Through a large scale survey, interviews and a small scale questionnaire, the thesis identifies key problems facing the schools from students and parents, and it reveals that many of Macao’s secondary schools are ill-equipped to handle these, and there are many signs that the problems are becoming more acute. The thesis finds that negative parental behavior has had a stronger effect on students than positive parental behavior, and it finds that there are several reasons why the schools, in their present state, cannot address these matters effectively. A significant gap is found between what the schools indicate they should be doing and what they are actually doing to address increased parental involvement in order to impact positively on Macao’s students. Recommendations are made for intervention and action
Keywords: PhD in Education (D-SE); Thesis and Dissertations; University of Saint Joseph

A mathematics curriculum or lower secondary schools in Macau - Wong, Kin Ming (University of Saint Joseph, 2009)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

English learning strategies and strategy instruction: a mixed methods study of EFL students in higher education - Chan, Mei Lan (University of Saint Joseph, 2015)
This thesis investigates the Language Learning Strategies (LLS) used by English as a Foreign Language (EFL) nursing students of higher education in Macao and the effectiveness related to students’ learning outcomes by Strategy Instruction (SI). To date there has been no literature in the area of SI among the Macao Chinese EFL higher education students on teaching all LLS groups, and on four main English skills to look at its effects on learning processes and outcomes at the same time, and this study starts to fill the gap. The research uses an embedded mixed methods research design in phase one and an embedded mixed methods quasi-experimental design in phase two. Phase one aimed to identify students’ LLS use. The findings revealed that students’ cognitive, metacognitive and compensatory strategies were used more than affective, memory-related and social strategies, and overall they used a medium to low level of LLS. In phase two, the effects of SI on students’ changes of LLS use, their proficiency and English learning processes were identified. After SI, students used LLS both more widely and frequently in all four main English skills. Most students’ motivation and self-confidence were enhanced. After SI the affective group of strategies in the treatment group statistically significantly improved, with a moderate effect size, from that of the comparison group. It was found that the widely used Strategy Inventory for Language Learning questionnaires by Oxford (1989c) had limited statistical power and some conceptual confusion. Recommendations are made for policy and practice of EFL instruction
Keywords: PhD in Education (D-SE); Thesis and Dissertations; University of Saint Joseph

Using Collaborative learning and blended learning with Macau undergraduate students inside and outside university classroom - Monteiro, Elisa Pack Jon Fong Rendall (University of Saint Joseph, 2015)
This thesis reports a mixed methods empirical research which included a university-wide survey and action research in form of a quasi-experiment in collaborative blended learning (CBL) with Macau undergraduate students. The intervention embodied the principles of social constructivism and investigated the putative benefits and challenges of CBL. The purpose of the study was to identify how to promote effective CBL in undergraduate students and to increase effective learning, motivation, autonomy, empowerment, and communication. It found that only small improvements to students’ CBL took place over time, and found that the students needed specific instruction, practice and development in how to collaborate, both with and without online learning. Despite being in a world-leading, enriched digital environment, the students were new to collaboration and online learning. Students discovered and appreciated the benefits and challenges to collaboration and CBL largely by doing it. The thesis shows that CBL does not release teachers from their instructional and pedagogical roles; rather they place teachers at the heart of effective practice and improvements. The study underpins the need for explicit training of students in CBL. It identifies several strategies and tools which can be useful to promote effective genuine CBL
Keywords: PhD in Education (D-SE); Thesis and Dissertations; University of Saint Joseph

An investigation into students' views of the backwash effects of the English section of the joint admission examination for Macau four higher education institutions (languages and mathematics) - Bramley, Corinna Elaine (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Curriculum leadership and management - San, Pek Leng (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Teachers’Perceptions of Performance Appraisal in a Secondary School in Asia: A Case Study - Potger, Matthew Rodney (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

SENIOR LEARNERS, ANDRAGOGY, GERAGOGY, AND SYNTHETIC PHONICS: A CASE STUDY - Bhroin, Aine Ni (University of Saint Joseph, 2023)
Although there is a substantial body of research on the second language acquisition of adults, there is little specific research on the learning experiences of senior and very senior adults. This thesis investigates and discovers the experience of being a senior from a traditional Confucian Heritage Culture aged between 55 and 75 years old, learning English as a foreign language through various interventions, including, the introduction of an adapted version of synthetic phonics to improve pronunciation, alongside the use of andragogical and geragogical principles to accommodate and encourage the development of agency and self-directed learning. This research adopted a case study methodology to investigate the lived experiences of seniors, and investigated the participants’ subjective constructions of the situation, learning experiences, challenges, circumstances, needs, and wants with regard to the situation. Therefore, an open and exploratory case study design was selected to understand the participants and report the findings. Furthermore, this thesis identifies the challenges faced by senior and very senior learners who are post-work and post-family rearing to make recommendations from the findings to complement, enhance and empower their learning
Keywords: ANDRAGOGY; GERAGOGY; SENIORS; SYNTHETIC PHONICS; Thesis and Dissertations PhD in Education (D-SE); University of Saint Joseph